Three Pillars of the Organizational Cultural Framework and Interpersonal Skill of Creative Economy Entrepreneurs in Jakarta - Aristo Surya Gunawan; Ati Cahayani (Indonesian Journal of Business Analytics, 2026)
Organizational culture and interpersonal skills influence organizational or entrepreneurial performance. Meanwhile creative economy emerges as one pillar of Indonesian economy. This article aims to exercise three pillars of organization culture and interpersonal skills that are important for entrepreneurs in creative industry. This research is using qualitative methodology and 15 informants of creative economy entrepreneurs in Jakarta. As the result these three organization culture pillars are closely linked to the four indicators of interpersonal skills. These interpersonal skills play a crucial role in reinforcing organizational culture and ensuring those cultural pillars are maintained in daily business operations